Foreign experience of administrative and legal regulation of activities of bodies of justice - Mentukh, Nataliia; Shevchuk, Oksana (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article is devoted to analysis of theoretical and practical issues of administrative and legal status of the justice authorities. Administrative and legal relations in the justice authorities’ sphere are circled. The analysis of foreign experience in the organization of justice authority of the regional level is made offers on improving legal base in the sphere are formulated.